Knowledge, Attitude and Practice of Breast Feeding among Bote Women - Rana, Khim Bahadur (Prāgyik Prabāha, 2023)
Breast feeding is vital to a baby's health. Milk is unique food adapted to nutritional needs of offspring in mammals. Breast milk is the healthiest food for the child. The main objective of this study is to identify the practice of breastfeeding among the Bote women. In this study, the simple random sampling method was used. Among the 140 Bote households, 52 individual Bote women were selected from the households. The study shows that low literacy, poor income and lack of access to communication lead them to traditional practices. Increasing access to education, communication media, awareness programs and healthcare facilities helps them to improve their knowledge, attitudes and practices about breastfeeding.